FACTORS AFFECTING ON LEADERSHIP OF FEMALE LECTURERS IN A UNIVERSITY, GUANGXI PROVINCE, CHINA - Cao , Jiabao; Santiparp, Prasak (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The main problems of leadership among female in higher education system are difficulty of women balancing the relationship between family responsibilities and work needs in the path of obtaining the top leadership. This research aims to compare whether there was any statistically significant difference in the levels of leaderships among female lecturers based on their personal factors. A research was surveyed leaderships and their related factors among female lecturers in a university at Guanxi, China. In order to conduct this research, data were gathered using the survey questionnaire, which tested for validity and reliability (Chronbac’s alpha = 0.947) already. From 1,087 female lecturers, the calculated sample size and multistage proportional sampling were done. The voluntary 284 female lectures were included in this research. The analytic statistics were ANOVA and Pearson’s correlation. The results showed that the significant levels of teachers’ leaderships by age, highest education levels, marital status, number of children, work experiences, social and psychological factors. The suggestions were decreased family responsibilities and social with psychological supporting for promoting leaderships of female lecture.